Physical Environment of Stilted Buildings in Rural Area of Southwest China. (2015) - Ma, Hongbo; Zhuang, Zhi; Ye, Hai; Cheng, Jun; Chen, Jiao; Qin, Bin
Abstract: Stilted building is a unique kind of buildings distributed across the southwest mountainous area in China, especially the Miao and Dong dwellings in Qiandongnan area. In this paper, two local traditional stilted houses, old-fashioned and new-fashioned, were selected for case study to investigate indoor environmental quality by field survey. The indoor thermal, luminous and acoustic environment and CO2 concentrations were tested and evaluated. Results indicated that the electric heating cannot meet the comfort requirements due to the bad thermal performance of the wooden envelope, while heating by the coal stove would cause indoor air pollution. The sound resistance effect of the wooden fabric is so poor that indoor human activities can bring the noise interference to the adjacent room. In addition, the indoor natural lighting illumination was much lower than the standard requirements due to improper interior space layout design, such as few windows with small open area. It is necessary to improve indoor environment for this traditional house for sustainable development. In this study, the indoor environmental conditions in the local traditional houses was objectively evaluated, which helps to guide the residence retrofit and improve indoor environment in the future.